Pancreatic resection in the pediatric, adolescent and young adult population: nationwide analysis on complications. Issue 8 (August 2021) - Pranger, Bobby K.; van Dam, Jacob L.; Groen, Jesse V.; van Eijck, Casper H.; Koerkamp, Bas G.; Bonsing, Bert A.; Mieog, J.Sven D.; Besselink, Marc G.; Busch, Olivier R.; Kazemier, Geert; de Jong, Koert P.; de Kleine, Ruben H.J.; et al.
Abstract: Background: The aim of this study was to determine pancreatic surgery specific short- and long-term complications of pediatric, adolescent and young adult (PAYA) patients who underwent pancreatic resection, as compared to a comparator cohort of adults. Methods: A nationwide retrospective cohort study was performed in PAYA patients who underwent pancreatic resection between 2007 and 2016. PAYA was defined as all patients <40 years at time of surgery. Pancreatic surgery-specific complications were assessed according to international definitions and textbook outcome was determined. Results: A total of 230 patients were included in the PAYA cohort (112 distal pancreatectomies, 99 pancreatoduodenectomies), and 2526 patients in the comparator cohort. For pancreatoduodenectomy, severe morbidity (29.3% vs. 28.6%; P = 0.881), in-hospital mortality (1% vs. 4%; P = 0.179) and textbook outcome (62% vs. 58%; P = 0.572) were comparable between the PAYA and the comparator cohort. These outcomes were also similar for distal pancreatectomy. After pancreatoduodenectomy, new-onset diabetes mellitus (8% vs. 16%) and exocrine pancreatic insufficiency (27% vs. 73%) were lower in the PAYA cohort when compared to adult literature. Conclusion: Pancreatic surgery-specific complications were comparable with patients ≥40 years. Development of endocrine and exocrine insufficiency in PAYA patients who underwent pancreatoduodenectomy, however, was substantially lower compared to adult literature.